2017
DOI: 10.1097/acm.0000000000001667
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting and Retaining Community-Based Preceptors: A Multicenter Qualitative Action Study of Pediatric Preceptors

Abstract: Changes in health care delivery have imposed more time constraints on community-based preceptors. However, this study identified underlying factors motivating physicians to volunteer as preceptors. Strategies to recruit new and retain current preceptors must be collaborative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…Concerns that teaching will increase working time and decrease productivity were rated as most important barriers. These findings are supported by studies from other countries [18, 19, 28] as well as by a recent survey among German GPs [14]. And indeed, it has been clearly shown that prolonged working time and reduced numbers of patients treated are realistic consequences of teaching students [7, 15, 17, 29, 30].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Concerns that teaching will increase working time and decrease productivity were rated as most important barriers. These findings are supported by studies from other countries [18, 19, 28] as well as by a recent survey among German GPs [14]. And indeed, it has been clearly shown that prolonged working time and reduced numbers of patients treated are realistic consequences of teaching students [7, 15, 17, 29, 30].…”
Section: Discussionsupporting
confidence: 61%
“…Results of a recent study from Canada imply that a good support for teaching by the local department is positively associated with the overall job satisfaction of family medicine faculty members teaching students in community-based settings [26]. Other studies described the particular significance of rewards like public recognition, continuing medical education (CME) credits, bookstore discounts, access to computer networks, and workshops to improve clinical teaching [27, 28], which were rated as less relevant in our study. Concerns that teaching will increase working time and decrease productivity were rated as most important barriers.…”
Section: Discussionmentioning
confidence: 99%
“…This national random sample survey with RDN and NDTR professionals identified differences by preceptor experience category in attitudes and perceptions of the dietetic internship preceptor role, institutional support, intern value, and preferred incentives to precept. Despite the important role preceptors perform by supervising dietetic interns during their experiential learning, little research has been conducted examining these aspects of the precepting experience for the dietetics profession [12][13][14][15][16][17][18], although other health professions have explored the precepting experience [6][7][8][9][10][11]20]. If the dietetics profession hopes to address the imbalance between didactic program graduates and available internship positions [3,4], and address the needs of the workforce by keeping up with the growth rate of the number of jobs for RDNs [1], additional preceptors will be needed to increase experiential learning opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…While other health professions have explored the attitudes and perceptions associated with precepting, including the desired benefits and perceived barriers associated with the role [6][7][8][9][10][11], limited research has been conducted in the area of nutrition and dietetics despite the critical role preceptors play in the education and training of future RDNs and NDTRs [12][13][14][15][16][17][18]. Understanding what motivates practitioners to not only become preceptors, but to continue precepting, as well as the barriers to serving as a preceptor, is important if the dietetic profession is to successfully recruit sufficient preceptors now and in the future.…”
Section: Introductionmentioning
confidence: 99%
“…J o u r n a l P r e -p r o o f preceptors suggested creative scheduling to maximize patient flow in clinics or working with nurses to do patient in-takes or vaccinations as options. 12 Additionally, Penn State Hershey trained students as patient navigators, care transition facilitators, or quality improvement extenders. 13,14 These recommendations for recruiting preceptors coincided with parallel pressures on outpatient practices to meet quality metrics.…”
mentioning
confidence: 99%